Early Miscarriage of Unwanted Pregnancy After Radioiodine Ablation in a Patient with Graves’ Disease: Case Report - Zerin, Fariha; Mahmud, Sujon; Jannat, Md Sifat Meftaul; Akter, Yeasmin; Hasan, Bahalul; Chowdhury, Md Sunny Anam (Bangladesh Journal of Nuclear Medicine, 2024)
Graves. disease in females of childbearing age is common. Radioiodine therapy (RAIT) is a definitive treatment for such a condition. The effect of radiation on germ cells and iatrogenic hypothyroidism following radioiodine therapy may cause a bad pregnancy outcome. We present an unfortunate case of miscarriage of early pregnancy in 7th gestational weeks following 7 months of RAIT and an approach to the clinical question .How to manage Graves. disease with RAIT in women of childbearing potential.. Maintenance of an adequate interval and achieving euthyroid status after RAI ablation in Graves. disease in patients willing to conceive can reduce the risk of miscarriage and assure a good pregnancy outcome. Bangladesh J. Nuclear Med. 26(2): 201-203, 2023